(untitled) (Global Journal of Medical Research, 2020)
The objective of this work is to determine the Technical Efficiency for a set of Hospitals of the National Health System of Chile for the periods 2015 and 2016. The methodology to be used is the DEA-CCR data analysis and DEA-BCC Orientation Inputs. The inputs variables are the number of doctors, dentists, nutritionists, nurses, kinesiologists, midwives, medical technicians, paramedics, and number of beds. As Output hospital discharges. The results showed that, in the case of Model 1 DEA-CCR, the hospitals that improved their efficiency scores were Tarapacá (100), Coquimbo (91) and Araucanía (100). In the other Regions there has been a decrease in their efficiency scores. In the second phase of the study, a linear regression model was used to quantify the effect of the variable medical personnel and hospital discharges. The results found a positive and statistically significant effect of the medical staff variable on hospital discharges. In other words, with an increase of one percentage point in medical personnel, hospital discharges would increase by 36.1 percentage points. On the other hand, the same analysis did not find that an increase in the medical staff will improve efficiency rates.